Judicial Effectiveness in Corruption Sentencing: An Analysis of Proportionality and Deterrent Impact in Indonesia's Anti-Corruption Court System (International Forum of Researchers and Lecturers, 2025)
Corruption remains one of Indonesia's most pressing legal challenges, causing substantial state financial losses and impeding national development. This study analyzes the effectiveness of court decisions in imposing sentences on corruption perpetrators from both proportionality and deterrence perspectives. Using socio-legal research methodology with descriptive analysis, this research examines (1) the extent to which judicial decisions reflect principles of proportional justice in corruption sentencing, and (2) the deterrent impact of such sentences on both individual offenders and potential perpetrators. Data were collected through comprehensive documentation study of corruption court decisions, statutory analysis, and review of relevant legal literature. Findings reveal significant sentencing disparity across similar corruption cases, with most sentences imposed near minimum statutory thresholds despite massive state losses. The average imprisonment duration for corruption offenses is only 2 years and 8 months, substantially below maximum allowable sentences. This study identifies both juridical factors (wide sentencing ranges, evidentiary weaknesses) and non-juridical factors (political intervention, defendant's social status) as primary obstacles to effective sentencing. The research concludes that current judicial practices fail to achieve optimal deterrent effects, as evidenced by high recidivism rates and continued corruption prevalence. Comprehensive reforms in sentencing guidelines, judicial capacity building, and monitoring mechanisms are essential to enhance the effectiveness of anti-corruption judicial processes in Indonesia.